2011
DOI: 10.1097/mpg.0b013e318230146c
|View full text |Cite
|
Sign up to set email alerts
|

Widening Spectrum of Liver Angiosarcoma in Children

Abstract: Careful follow-up is necessary to detect late recurrence in infants with multinodular liver hemangiomas. Vascular liver tumors occurring after infancy are likely to be malignant. The high risk of relapse in the remaining liver suggests that if no metastases are detected, liver transplantation is preferable to surgical tumor resection in both situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“… 14 – 16 Ackermann et al has reported a large tumor of IHH type 2 with early central enhancement. 6 To our knowledge, diffuse IHH with early central enhancement has not previously been reported in the English literature. In this case, the reason of central enhancement was unclear.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“… 14 – 16 Ackermann et al has reported a large tumor of IHH type 2 with early central enhancement. 6 To our knowledge, diffuse IHH with early central enhancement has not previously been reported in the English literature. In this case, the reason of central enhancement was unclear.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, a mixture of type 1 and type 2 components within the same liver has been reported. 5 , 6 IHH may be solitary, multifocal, or diffusive. The diffuse lesions are all classified as type 2.…”
Section: Discussionmentioning
confidence: 99%
“…There is a reported female predominance within the cases, and the median age is reported to be 40 months [ 62 , 65 , 66 ]. We were able to find 72 published cases of pediatric hepatic angiosarcoma since 1944 ( Supplemental Table S1 ) [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Malignant Tumors In Infants and Early Childhoodmentioning
confidence: 99%
“…Laboratory evaluation may be notable for consumptive coagulopathy and anemia. AFP is typically normal, as are other common tumor markers, although elevated β-hCG has been reported [ 62 , 63 , 66 , 80 , 88 ]. Pulmonary metastasis is common [ 63 ].…”
Section: Malignant Tumors In Infants and Early Childhoodmentioning
confidence: 99%
See 1 more Smart Citation